Make “Incongruent” to Be “Excellent”: Fluid Compensation in Extremely Incongruent New Products - Leng, Xionghui; Chen, You; Song, Xinyu; Zhou, Xiaoyu; Li, Xi (Frontiers in Psychology, 2022)
Under fierce market competition, firms are accelerating the pace of product innovation which may bring extremely incongruent new products. Generally, consumers are unfamiliar with extreme incongruence, resulting in passive product evaluation and a low success rate. This study draws on the meaning maintenance model of fluid compensation theory to examine how extremely incongruent new products influence product evaluation. Three experiments indicate that consumers’ product evaluation of extremely incongruent new products is significantly lower than that of congruent products, and it can be notably improved by three ways of fluid compensation. The findings reveale that anxiety moderates the relationship between extremely incongruent new products and product evaluations, and further self-esteem moderates the relationship on the main effects. Overall, our research reconciles divergent findings on the effect of extremely incongruent new products on the effects of product evaluation and further provides rich managerial implications for product innovation management.